Do not disturb! : a student developed 3-D generated (CG) animated short. - Hisyam Abdul Rahman. (2011)
This report will discuss the procedures, techniques and processes involved in creating a short 3-D computer animated film entitled ‘Do Not Disturb!.’ It will also reveal the problems faced during the development of this project as well as the attempts at solving them, whether successfully or otherwise. In addition, it will track down the author’s progress and involvement in the production stages throughout the film. It is not meant to be an autobiographical account but of a ‘behind the scenes’ journal in the making of an independently produced short film.